Comparative genomics‐informed design of two LAMP assays for detection of the kiwifruit pathogen Pseudomonas syringae pv. actinidiae and discrimination of isolates belonging to the pandemic biovar 3. (6th June 2016) - Ruinelli, M.; Schneeberger, P. H. H.; Ferrante, P.; Bühlmann, A.; Scortichini, M.; Vanneste, J. L.; Duffy, B.; Pothier, J. F.
Abstract : The aim of this study was to develop a rapid, sensitive and reliable field‐based assay for detection of the quarantine pathogen Pseudomonas syringae pv. actinidiae (Psa), the causal agent of the most destructive and economically important bacterial disease of kiwifruit. A comparative genomic approach was used on the publicly available Psa genomic data to select unique target regions for the development of two loop‐mediated isothermal amplification (LAMP) assays able to detect Psa and to discriminate strains belonging to the highly virulent and globally spreading Psa biovar 3. Both LAMP assays showed specificity in accordance with their target and were able to detect reliably 125 CFU per reaction in less than 30 min. The developed assays were able to detect the presence of Psa in naturally infected kiwifruit material with and without symptoms, thus increasing the potential of the LAMP assays for phytosanitary use.